The Antiviral Activity of GcMAF in the Treatment of Experimental Animals Infected with SARS-CoV-2 - Anastasia S. Proskurina; Oleg S. Taranov; Svetlana S. Kirikovich; Svetlana V. Aidagulova; Elena K. Ivleva; Andrey V. Shipovalov; Gleb A. Kudrov; Sergei A. Bodnev; Alena S. Ovchinnikova; Anna V. Zaykovskaya; Oleg V. Pyankov; Evgeniy V. Levites; et al. (COVID)
Despite the end of the COVID-19 pandemic, there still remain risks of new aggressive strains of coronavirus. As the human population increases progressively, it is mandatory to ensure both preventive measures and an immediate response to emerging infectious threats. Another essential component for rapidly restraining a new possible pandemic is the development of new anticoronaviral therapeutics. In the present study, the anticoronaviral capabilities of Gc protein-derived macrophage-activating factor (GcMAF) are characterized. It is demonstrated that the administration of GcMAF to Syrian hamsters infected with SARS-CoV-2 within the first phase of infection (six days postinfection) is accompanied by (i) a statistically significant reduction in the viral load of the lung tissue and (ii) the switching of the inflammatory status of the lung tissue to a neutral one in terms of mRNA expression levels of the groups of pro/anti-inflammatory cytokines and chemokines. The potential mechanism for this antiviral action and the containment of the inflammatory response by the drug associated with the engagement of terminal N-acetylgalactosamine GcMAF and C-type lectin domain containing 10A expressed at the surface of lung-infiltrating macrophages and pneumocytes, which simultaneously express angiotensin-converting enzyme 2, is discussed.